Introduction to basic offensive fighter manoeuvres - Pantelatos, Dimitri (Cranfield University, 1997)
The contents of this report were presented during a talk to the Flight Dynamics and Aerodynamics MSc and PhD students, arranged and supported by the Flight Dynamics Group of the College of Aeronautics. This talk took place on 17th March 1997 in lecture room C of the College of Aeronautics. These contents are published under permission of the Hellenic Air-Force according to OGHA4395.GEE/28-5-97/10:20: 19 document. The aim of this report is, by gathering essential information from the air combat literature and relating this information with personal experience, to provide knowledge about the practical application of some aspects of the Flight Dynamics lecture course material.